KONSEP PENDIDIKAN HUMANIORA TERHADAP MAKHLUK BERBUDAYA - Herina, Herina (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The purpose in this discussion is to know the concept of humanities education towards cultured beings. Cultivated beings are known to be human beings are expected to be able to make humanities education as an effort to become human more human. This humanity presents the educational material depicting human wholeness which means putting human beings in the midst of the educational process which includes three things as follows (1) menyatrazapkan development of mind and (ratios) with the heart (taste) (2) introduce to students the values of humanity universal and eternal. (3) to prioritize cooperation between the concept of education and students and between the theories taught, then practiced in life. The sample of this discussion is the human being who is regarded as the most cultured and intellectual creature, which is essentially intellect and mind are two possessions possessed by the human soul and is expected with the human mind and mind to utilize the wealth for the essential needs of life. And as a guide to live in society.Keywords: humanities, human beings, human beings